Generational Transmission – Transmission of Values in a Family in the Context of the Church Teaching, Information on the Research of the Youth from Warmian-Masurian Voivodeship - Wójcik, Piotr (Studia Warmińskie, 2014)
The family realises a process of children’s socialization, transmission of values, generational transmission, learning about their social roles, skills, life in the society - the acquisition of cultural competence, learning the foundations of cultural capital, which consists of ideas, knowledge, skills and items of cultural values that people acquire during their participation in social life. Yet, not always does the family function in a way that allows the formation of a man who is open, thinking, able to live in the society, so as to equip that man in the appropriate cultural capital, in cultural competence. Some families are subject to dysfunctions at various levels. Apart from the easiest to enumerating dysfunctions such as: addictions or poverty, it is crucial to point to the shrinking time budget in families that are absorbed by gainful employment, the absence of one of the parents or living with a cohabitee of a parent. In the recent years, the community of the family time has been even more decreased by the labour migration of parents, and the absence of the mother has a particularly strong impact on the assessment of the family relationships. Sociology, examining the value system, helps to diagnose the changes - the transformation of values - and it aids to indicate, for instance, to the priesthood, the potential opportunities of participating in the formation, particularly by young people, of the systems of values based on the moral indications of the Church teaching.